Review paperContemporary methods of imaging diagnostic of osteoporosis in rheumatic diseases - Zawirski, Piotr; Rell-Bakalarska, Maria; Łącki, Jan K. (Reumatologia/Rheumatology, 2008)
Patients with rheumatic disease are at a higher risk of osteoporosis and low-energy fractures compared to the general population. Bone loss is associated not only with inflammatory activity and corticosteroid use but also loss of capability to manage activities of daily life. Dual-energy X-ray absorptiometry (DXA) is the standard method for diagnosis of osteoporosis in such cases. Because of the specificity of rheumatic diseases DXA has limited diagnostic application and therefore in clinical practice other methods are useful for diagnosis and prognosis of risk of fracture. However, identification and prediction of non-skeletal risk factors in the population with rheumatic diseases are necessary to define the therapeutic threshold in particular diseases.